Workshop Live Streaming Menggunakan OBS Untuk MGMP TIK Pekanbaru - Ibnu Surya; Ivan Chatisa; Yoanda Alim Syahbana; Muhammad Ihsan Zul; Yuli Fitrisia; Jan Alif Kreshna; Harumin Harumin; Irgi Yoga Pangestu (Jurnal Pengabdian Kompetitif, 2026)
OBS is open-source software that needs to be introduced to the community, particularly to organizations and companies with a high demand for live streaming communication. This needs to be introduced and optimized because the infrastructure is generally already available and running well and is almost evenly distributed among certain organizations, both companies and high schools. OBS can be applied for streaming communication purposes on Internet-based networks. This activity is a PkM, which is a collaboration between Polytechnic Caltex Riau and the Information and Communication Technology Subject Teacher Working Group (MGMP TIK) in Pekanbaru and Kampar, Riau. Live Streaming Workshop/training using OBS to introduce and deepen the material for ICT teachers to teach multimedia network material, streaming technology. For this purpose, training and evaluation were conducted before and after the workshop on teachers' knowledge of live streaming. Prior to the workshop, approximately 79% understood the material, After being introduced to the participants and trying out the practice, results showed that approximately 100% found it easy to understand and could be applied to support multimedia network practical work.